High performance liquid chromatography for simultaneous determination of xipamide, triamterene and hydrochlorothiazide in bulk drug samples and dosage forms - Abd El-Hay Soad S.; Hashem Hisham; Gouda Ayman A. (Acta Pharmaceutica)
A novel, simple and robust high-performance liquid chromatography (HPLC) method was developed and validated for simultaneous determination of xipamide (XIP), triamterene (TRI) and hydrochlorothiazide (HCT) in their bulk powders and dosage forms. Chromatographic separation was carried out in less than two minutes. The separation was performed on a RP C-18 stationary phase with an isocratic elution system consisting of 0.03 mol L−1 orthophosphoric acid (pH 2.3) and acetonitrile (ACN) as the mobile phase in the ratio of 50:50, at 2.0 mL min−1 flow rate at room temperature. Detection was performed at 220 nm. Validation was performed concerning system suitability, limits of detection and quantitation, accuracy, precision, linearity and robustness. Calibration curves were rectilinear over the range of 0.195–100 μg mL−1 for all the drugs studied. Recovery values were 99.9, 99.6 and 99.0 % for XIP, TRI and HCT, respectively. The method was applied to simultaneous determination of the studied analytes in their pharmaceutical dosage forms.